2022
DOI: 10.1017/s0022109022000564
|View full text |Cite
|
Sign up to set email alerts
|

Taxing the Disposition Effect: The Impact of Tax Awareness on Investor Behavior

Abstract: Standard portfolio choice models predict that investors consider the tax implications of trading. However, individuals are disposed toward realizing gains and holding losing investments, behaviors that worsen their performance. We show, in an experimental market, that increasing tax salience reduces the disposition effect between 22% and 47%, leading to higher portfolio balances without increasing total trading activity. Using field data, we find that investors’ disposition is sensitive to taxes around tax rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 137 publications
1
3
0
Order By: Relevance
“…On similar lines, observations were made by [39]. It is found that the DE is sensitive to taxes and the decisions of traders are affected by the rate of taxes [40]. In this context [41], observed the impact of security transaction taxes and inferred that it has an adverse impact on stock market participants and reduces profitability.…”
Section: Cost-consciousnesssupporting
confidence: 53%
See 1 more Smart Citation
“…On similar lines, observations were made by [39]. It is found that the DE is sensitive to taxes and the decisions of traders are affected by the rate of taxes [40]. In this context [41], observed the impact of security transaction taxes and inferred that it has an adverse impact on stock market participants and reduces profitability.…”
Section: Cost-consciousnesssupporting
confidence: 53%
“…The options traders are aware of the transaction charges and taxes they incur, and they devise their risk-reward ratios accordingly, thus, costconsciousness is found to be a non-significant element. It is also observed by [40] that the effect of taxes and other costs is significant when the financial year ends, V. Choubey, P.V. Joshi but short term option trading doesn't get affected by these costs.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from emotional factors, some of the possible drivers of the bias include cognitive dissonance (Altanlar et al , 2019), (Chang et al , 2016), belief-based trading (Ben-David and Hirshleifer, 2012), investor demographics and socio-cultural factors (Zhang et al , 2022). Despite the extent of research on the issue, the empirical evidence on the factors behind the disposition effect is still inconclusive (Bazley et al , 2022), making it an interesting area for research.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on the phenomenon has found that it reduces investors’ profits due to accumulation (Odean, 1998), underreaction to announcements leading to price deviations and mispricing in the market (Frazzini, 2006). Also, it influences the aggregate market by its impact on returns, volatility and trading volume (Bazley et al , 2022). Although the disposition effect also impacts mutual fund managers’ work (Bharandev and Rao, 2020), the bias is more costly for individual investors (Odean, 1998; Chen et al , 2007).…”
Section: Introductionmentioning
confidence: 99%